2020
DOI: 10.5195/cajgh.2020.440
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors Associated with Bottle Feeding Practices in Infants Under Two Years of Age: A hospital-based study in Woldia, Ethiopia

Abstract: Introduction: Bottle feeding should be avoided when possible in infants under the age of two to improve health outcomes. The magnitude of bottle feeding practice is currently increasing in Ethiopia, however factors associated with bottle feeding usage are rarely addressed in research. We aimed to fill this gap and assess the magnitude of bottle feeding and its association with sociodemographic factors among infants in Woldia, Ethiopia in 2019.Methods: A hospital-based cross-sectional study was conducted in Wol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…This is in line with a study conducted in Ghana [14]. But lower than a study conducted in Indonesia [34], Pakistan [35], Eastern Sudan [36], and studies conducted in different districts of Ethiopia [2,15,37]. This difference might be due to the variations in socio-cultural aspects of the study participants regarding child feeding practices.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is in line with a study conducted in Ghana [14]. But lower than a study conducted in Indonesia [34], Pakistan [35], Eastern Sudan [36], and studies conducted in different districts of Ethiopia [2,15,37]. This difference might be due to the variations in socio-cultural aspects of the study participants regarding child feeding practices.…”
Section: Discussionsupporting
confidence: 87%
“…According to this study, as the age of the child increase, the chance of having bottle feeding increases. This is supported by a study conducted in Woldia Ethiopia [37], Holeta central Ethiopia [2], Namibia [13], Indonesia [34] which showed that children aged 6-23 months were more likely to use bottle feeding as compared to children aged 0-5 months. This is because, as child get older, they may have more feeding options, such as consumption of water, tea, and processed milk which may lead to a higher rate of bottle feeding On the other hand, children who are found aged 0-5 months had no well-matured gastrointestinal systems then bottle feeding during this age may be associated with problems in digestion and absorption, which eventually lead to diarrhea, vomiting, and infections.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Similarly, regarding the number of living children, the search results offer data on the prevalence of and factors associated with bottle feeding practices with infants under the age of two. It was discovered that having 2–5 children was substantially connected with bottle feeding practice [ 30 ]. This may be related to older mothers and the resource shortage mentioned in the previous sections.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that as children grow older, they may have more feeding options, such as drinking water, tea, and processed milk, which may result in a higher rate of bottle feeding [ 26 ]. Mothers with such prior experience may be less likely to start bottle feeding their child at a young age [ 30 ]. Women who are urban, educated, or empowered are more likely to attend health facilities while pregnant [ 31 ].…”
Section: Discussionmentioning
confidence: 99%